An Examination of How a Coach of Disability Sport Learns to Coach from and Through Experience - Duarte, Tiago (Université d'Ottawa / University of Ottawa, 2013)
Despite the steady growth of coaching science over the last two decades, research on coaches of persons with disabilities is scarce. This study examined how an adaptive sailing coach learned through and from experience using a single case study methodology. Jarvis’s (2009) lifelong learning approach and Gilbert and Trudel’s (2001) reflective conversation model framed the thematic analysis. The findings revealed that the coach, Jenny, was exposed to collaborative environments that optimized her learning process. Social interactions with a number of people (e.g., mentors, colleagues, and athletes) possessing different types of expertise made major contributions to Jenny becoming a coach. As time progressed and Jenny was exposed to a mixture of challenges and learning situations, she advanced from recreational Para-swimming instructor to developmental adaptive sailing coach. This study informs future research in disability sport coaching.
Keywords: lifelong learning; reflection; life-story; adaptive sailing